Bukan hanya Tugas Istri: Pengaruh Penggunaan Kontrasepsi Suami terhadap Kesehatan Mental Istri - Saputra, Aldo Savira Adha; Pardede, Elda L. (UI Scholars Hub, 2026)
Male participation in contraceptive use in Indonesia remains very low, while women continue to bear a disproportionate reproductive burden, including mental health impacts from contraceptive side effects. This study aims to examine the effect of husbands’ contraceptive use on wives’ mental health. The analysis utilizes data from the fifth wave of the Indonesia Family Life Survey conducted in 2014. Wives’ mental health is measured using the Center for Epidemiologic Studies Depression Scale - 10. The results of the binary logistic regression model indicate that husbands’ contraceptive use lowers the likelihood of wives experiencing depression. Additionally, being aged 25-49, having good self-rated health, having autonomy in household decision-making, being active in social participation, having a higher level of household income, and living in a safe environment are associated with a lower likelihood of depression. Conversely, being employed, having a history of adverse pregnancy outcomes, having a chronic illness, and having four or more children are linked to a higher likelihood of depression. These findings highlight the importance of husbands’ involvement in contraceptive use as a form of social support that contributes positively to wives’ mental health and overall family well-being.